Body image and quality of life in patients with and without body contouring surgery following bariatric surgery: a comparison of pre- and post-surgery groups - de Zwaan, Martina; Georgiadou, Ekaterini; Stroh, Christine E.; Teufel, Martin; Köhler, Hinrich; Tengler, Maxi; Müller, Astrid (Frontiers in Psychology, 2014)
Background: Massive weight loss (MWL) following bariatric surgery frequently results in an excess of overstretched skin causing physical discomfort and negatively affecting quality of life, self-esteem, body image and physical functioning. Methods: In this cross-sectional study 3 groups were compared: 1) patients prior to bariatric surgery (n=79), 2) patients after bariatric surgery who had not undergone BCS (n=252), and 3) patients after bariatric surgery who underwent subsequent body contouring surgery (BCS) (n=62). All participants completed self-report questionnaires assessing body image (MBSRQ), quality of life (IWQOL-Lite), symptoms of depression (PHQ-9) and anxiety (GAD-7). Results: Overall, 62 patients (19.2%) reported having undergone a total of 90 BCS procedures. The most common were abdominoplasties (88.7%), thigh lifts (24.2%), and breast lifts (16.1%). Post-bariatric surgery patients differed significantly in most variables from pre-bariatric surgery patients; however, there were fewer differences between patients with and without BCS. Patients after BCS reported better appearance evaluation, body area satisfaction, and physical functioning, even after controlling for excess weight loss and time since surgery. No differences were found for symptoms of depression and anxiety, and most other quality of life and body image domains. Discussion: Our results support the results of longitudinal studies demonstrating significant improvements in different aspects of body image, quality of life, and general psychopathology after bariatric surgery. Also, we found better appearance evaluation and physical functioning in patients after BCS following bariatric surgery compared to patients with MWL after bariatric surgery who did not undergo BCS. Overall, there appears to be an effect of BCS on certain aspects of body image and quality of life but not on psychological aspects on the whole.